Pharmacopoeian Aspects of Suspensions Preparation in Pharmacy Conditions - Yuryeva, G. B. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: This study aims to analyze the classification, nomenclature, advantages of modern auxiliary substances, and prospects of using them in development of extemporal suspensions; to evaluate the pharmacopoeian requirements to extemporal suspensions preparation. Materials and Methods: In the work, the retrospective, logical, and analytical research methods have been used to analyze the data of special literature and regulatory framework. Results and Discussion: Based on the data of modern scientific literature, the requirement for extemporal suspensions is outlined. The detailed analysis of modern auxiliary substances (suspending agents, stabilizers, etc.) most often used and approaches to the choice of them in the process of suspensions development is given. Conclusion: Approaches to selecting of auxiliary substances have been considered. The monitoring of pharmacopoeian requirements demonstrated that the chemists require the detailed information about technologies, auxiliary substances, picking, and package/storage conditions for extemporal forms.